Use of a social jetlag-mimicking mouse model to determine the effects of a two-day delayed light- and/or feeding-shift on central and peripheral clock rhythms plus cognitive functioning. (4th March 2021) - Haraguchi, Atsushi; Nishimura, Yutaro; Fukuzawa, Miyabi; Kikuchi, Yosuke; Tahara, Yu; Shibata, Shigenobu
ABSTRACT: Social jetlag (SJL) is defined as the discrepancy between social and biological rhythms and calculated by the difference between the midpoint of sleep time on working-days and free-days. Previous human and mouse studies showed SJL is positively related to evening chronotype and significantly related to smoking habit, cardiovascular risk, cognitive ability, and that SJL-mimicking conditions, simulating the real lifestyle situation of SJL in many humans, disrupt the regularity of estrous cycles of female animals. The effects of SJL-mimicking conditions on circadian rhythms and cognitive function and the reasons why the discrepancy between social and biological rhythms is involved in SJL have not yet been investigated. Therefore, in this study, we utilized a mouse model of SJL-mimicking conditions – 6-hour delayed-light/dark (LD) conditions for 2 days and normal-LD conditions for the following 5 days – applied for several weeks during which biological rhythms were monitored. Circadian rhythms of central and peripheral clocks and metabolism of the mice under the SJL-mimicking condition were always delayed for 2–3 hours compared with those under the normal-LD condition. Moreover, SJL-mimicking conditions impaired their cognitive function using a novel object recognition test. Only the delayed timing of either the light phase of the LD or of feeding for 2 days, comparable to the free-days situation of humans, delayed the circadian staging of rhythms the following 5 days. Furthermore, sleep deprivation during the early mornings for 5 days, which is comparable to early rise times experienced by humans on working-days and does affect the staging of circadian rhythms (circadian misalignment schedule), delayed the locomotor activity rhythms the next 2 days, comparable to free-days in humans, which is similar to the lifestyle rhythm of the evening chronotype. Our results demonstrated that the circadian misalignment schedule for 5 days changed the locomotor activity rhythms the following 2 days to the evening chronotype, that light- and/or feeding-shift conditions for 2 days exacerbate SJL, and that SJL-mimicking conditions delay the metabolic rhythm and cause cognitive impairment.